Preoperative visual acuity of cataract patients at a tertiary hospital in sub-Saharan Africa: a 10-year review (2019)
Purpose: To determine the preoperative visual acuity of cataract patients over a 10-year period in a tertiary facility as a means of auditing the cataract surgical services. Methods: A retrospective study of patients with age-related cataracts who had cataract surgery performed between January 2007 and December 2016 at the University College Hospital, Ibadan. Systematic random sampling and probability proportionate to size were used to recruit a representative sample. Information on sociodemographic characteristics, preoperative visual acuity, ocular and systemic comorbidities were retrieved and analysed. Results: Of the 499 patients studied, males were 268 (53.7%) and their mean age was 67.69 ( }9.51) years. The predominant visual acuity was hand motion 184 (36.9%) and yearly mean preoperative visual acuity was in the range of 0.0037–0.04 decimal. Conclusion: The mean preoperative visual acuity of patients in this facility did not change over the 10-year study period. Mean value of preoperative visual acuity remained within the range of blindness and did not improve over the decade. This could either be a reflection of visual impairment at which our patients seek care or an indication of the range of visual acuities at which surgeons are willing to offer cataract surgery in our environment. This trend has negative implications on the burden of cataract blindness as it reflects poor coverage of surgery for other levels of visual impairment due to cataract.